Pemberdayaan Kelompok Wanita Tani Desa Sumber Sari dalam Pembuatan Pupuk Organik Cair Berkadar Nitrogen Tinggi untuk Mengatasi Kelangkaan Pupuk Anorganik - Zainal Abidin; Roby Roby; F. Silvi Dwi Mentari; Yuanita Yuanita; Nur Hidayat; Daryono Daryono; Laode Muh Asdiq Hamsin Ramadan; Andi Lelanovita Sardianti; Faradilla Faradilla; La Mudi; Riama Rita Manullang; Rusmini Rusmini; Haryatie Sarie; Ramadan Ramadan (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Community service is an important activity in increasing community capacity and welfare. In an effort to support sustainable agriculture, training on making liquid organic fertilizer (POC) with high nitrogen content aims to provide knowledge and skills to the community to use organic waste as a basic ingredient for fertilizer. Liquid organic fertilizer which has a high nitrogen content plays an important role in increasing soil fertility and plant productivity without damaging the environment. This training includes an introduction to organic materials that are easily available and available nearby, fermentation techniques, as well as methods for making appropriate POC to produce fertilizer with high nitrogen levels. This training also explained the ecological and economic benefits of using liquid organic fertilizer compared to synthetic chemical fertilizer. Training participants are taught from basic theory to practical application, so they can apply this knowledge to plants. With this training, it is hoped that the community can increase agricultural productivity, reduce dependence on chemical fertilizers, and create a friendlier and more sustainable environment.